The Altered Cast Technique: A Case Report - Singh, S K; Singh, R K; Suwal, P; Parajuli, P K; Limbu, I K; Basnet, B B (Journal of Nepalese Prosthodontic Society, 2020)
The altered cast impression technique is commonly used for the mandibular distal extension partially edentulous arches. The technique is relatively simple and improves the residual ridge to dentition relationship of the prosthesis. Due to the displaceability of the mucosa, free end saddles get displaced under occlusal load. A 45-year-female patient reported to the Department Of Prosthodontics and Crown-Bridge, College of Dental Surgery, B.P. Koirala Institute of Health Sciences, Nepal with a chief complaint of missing bilateral lower posterior teeth. Clinical examination revealed missing teeth w.r.t 36, 37, 45, 46, and 47. The treatment plan was made to rehabilitate the patient with removable partial denture using functional impression along with the altered cast technique. The altered cast technique is the best alternative technique in the case of distal extension cases because better tissue adaptability, proper extension of a denture base, equal stress distribution, better support, and stability can be achieved. Finally, increased patient comfort and function are obtained.